EFL Teachers' Professional Identity: A Critical Discourse Analysis /Identidad profesional de docentes de ingles como lengua extranjera: un analisis critico del discurso - Marcial, Jaime; Santos, Nora M. Basurto (PROFILE issues in teachers' professional development, 2025)
This study uses critical discourse analysis to explore the identities of three university English teachers. The research identifies ideological elements in language teaching and cultural transmission practices, following the post-structuralist literature on their role in shaping personal and professional identities. Findings are presented through extracts from narrative and semi-structured interviews, highlighting the political, cultural, academic, and personal subject positioning in teachers' discourse. Critical discourse analysis elucidated the participants' views on teaching and cultural practices on an ethical level. The conclusions propose a possible revision of their professional identities based on discourse analysis, contributing to a deeper understanding of teachers' responsibilities towards language education. This was done with the construction of an interpretative profile with prescriptive aspects to enhance each participant's teaching practice. Keywords: critical discourse analysis, EFL teachers, Mexico, professional identity Este estudio utiliza el analisis critico del discurso para explorar la identidad profesional de tres docentes universitarios de ingles. La investigation identifica elementos ideologicos en las practicas de ensenanza de lenguas y de transmision cultural, en la configuration de identidades personales y profesionales. Los hallazgos se presentan a traves de extractos de entrevistas narrativas que destacan el posicionamiento politico, cultural, academico y personal dentro del discurso de los docentes. El analisis critico del discurso dilucida las perspectivas de los participantes sobre la ensenanza y las practicas culturales en un nivel etico. Las conclusiones ofrecen una posible revision de sus identidades profesionales a partir del analisis del discurso y asi contribuyen a una comprension mas profunda de la responsabilidad docente en relation con la education linguistica. Palabras clave: analisis critico del discurso, identidad profesional, maestros de ingles como lengua extranjera, Mexico